2018
DOI: 10.1097/md.0000000000013602
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-like activities in patients with head-up tilt test-induced syncope

Abstract: The purpose of this study was to assess the prevalence and the characteristics of seizure-like activities during head-up tilt test (HUT)-induced syncope, in patients with suspected vasovagal syncope (VVS). We also evaluated the differences in hemodynamic parameters between patients with and without seizure-like activities.A total of 71 patients with suspected VVS, who showed syncope during HUT between October 2010 and May 2013, were analyzed. Electrocardiogram and hemodynamic parameters were continuously monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
7
0
1
Order By: Relevance
“…Patients with VVS may present myoclonic jerky movements or upward deviation of eyeball during syncopal episodes and be misdiagnosed as epilepsy (5,6). Besides, reports showed that 8 to 66% of patients with neurally mediated syncope experienced seizurelike activities at the time of syncope during HUTT (7,8). The hemodynamic parameters related to seizure-like activities during HUTT-induced syncope in adults were reported in the previous study (7).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Patients with VVS may present myoclonic jerky movements or upward deviation of eyeball during syncopal episodes and be misdiagnosed as epilepsy (5,6). Besides, reports showed that 8 to 66% of patients with neurally mediated syncope experienced seizurelike activities at the time of syncope during HUTT (7,8). The hemodynamic parameters related to seizure-like activities during HUTT-induced syncope in adults were reported in the previous study (7).…”
Section: Introductionmentioning
confidence: 75%
“…Passman et al demonstrated that patients with seizure-like activities had significantly lower systolic BP and HR, and more frequent asystole at the time of syncope during HUTT than those without seizure-like activities (8). In another study, patients with seizure-like activities during HUTT had a lower HR and more occurrence of asystole at the time of syncope (7). In our study, VVS children with seizurelike activities showed a lower HR at the time of syncope, but no significant difference in systolic BP was found between patients with or without seizure-like activities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Seizure-like activity was associated with low systolic blood pressures and bradycardia during head-up tilt test (HUT)-induced syncope in a study by Joo et al They found 47 of 71 (66.2%) patients undergoing HUT had some sort of seizure-like activity, including eye deviation and jerking movements, with 70.2% of those 47 patients showing both. 19 Sudden cardiac arrest is physiologically similar to (HUT)-induced syncope, with the primary problem being a sudden loss of brain perfusion. The short duration of seizure-like activity due to loss of perfusion to the brain or sudden asphyxia seems to be a distinction repeated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Òàêaeå ÏÎÏ ïðèìåíÿåòñÿ äëÿ èíäóêöèè ñèíêîïàëüíûõ ñîñòîÿíèé ó ïàöèåíòîâ ñ ðåçèñòåíòíîé ýïèëåïñèåé, ÷òî ïîçâîëÿåò âûÿâèòü ñî÷åòàíèå ýïèëåïòè÷åñêèõ è íåýïèëåïòè÷åñêèõ ïðèñòóïîâ èëè èñêëþ÷èòü îøèáî÷íûé äèàãíîç ýïèëåïñèè [11][12][13].…”
Section: Introductionunclassified